Pengaruh Harga, Kualitas Produk, Media Sosial Instagram Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Produk Skincare Rannia Di Kota Metro - Yunanda, Via; Suharto, Suharto (Universitas Muhammadiyah Metro, 2023)
Via Yunanda. 2022. Effect of Price, Product Quality, Instagram Social Media and Customer Satisfaction on Customer Loyalty in Rannia Skincare Products in Metro City. Essay. Management Studies Program. Faculty of Economics and Business. Metro Muhammadiyah University. Advisors (1) Dr. Suharto, S.E., M.M. (2) H. Suwarto, S.E., M.M. This study aims to determine the effect of Price, Product Quality, Instagram Social Media and Customer Satisfaction on Customer Loyalty in Rannia Skincare Products in Metro City. The type of research used in this study is quantitative research with a total of 100 respondents as a sample. The data used is primary data, namely the distribution of questionnaires in the form of a list of questions using a Likert scale which is distributed to customers. The statistical test used to test the existing hypothesis is using multiple linear regression analysis test and data processing is tested using the statistical packages for the social science (SPSS) version 25 program. Based on the results of statistical tests, it shows that price has a positive and significant effect on customer loyalty, product quality has a positive and significant influence on customer loyalty, social media Instagram has a positive and significant influence on customer loyalty, and customer satisfaction has a positive and significant influence on customer loyalty.